The Effect Of Using The Talking Stick Strategy On Increasing Students' Motivation To Learn Arabic - Aini, Nur; Taufiqurrochman, R.; Ifawati, Nur Ila (JURNAL IJ-ATL, 2024)
Effective learning strategies are the key to motivating students in the midst of increasingly complex educational challenges. Without sufficient motivation, students' learning potential is difficult to develop, even though the teaching methods used are very diverse. This study aims to analyze the effect of using the Talking Stick strategy to increase students' learning motivation. This research uses a quantitative approach. This approach is applied to certain samples or populations, whether randomly selected or not, with data collection using instruments and quantitative data analysis. The type of research used is experimental, which aims to determine the effect of an action and test hypotheses regarding the comparison of the effects of these actions. The results of this study indicate that the use of the Talking Stick strategy has a significant effect on increasing student learning motivation, with a significance value of 0.000, which means <0.05, so Ha is accepted and H0 is rejected. Significant differences can be seen from the comparison of pretest and posttest questionnaire results, where the pretest showed a value of 22.15 (44%, sufficient motivation) and the posttest reached 36.85 (74%, high motivation). This shows an increase in student motivation after being given the treatment, from the moderate category to the high.